Representasi Gender Dalam Film Pendek Pria Karya Yudho Aditya: - Ginting, Sofhia Rahmadani; Saqina, Elsa Khoriah; Sazali, Hasan; Dalimunthe, Maulana Andinata (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Recently, film has often become a means of communication that is used to convey sensitive messages or even those that are difficult to convey clearly, but in accordance with the realities that exist in society. Therefore, this research was conducted to identify gender identity in the film